Work Engagement as a Mediator of Transformational Leadership on Employee Performance - Rezeki, Fitri; Badrianto, Yuan; Ngudi Wijayanto, Tri; Ramadhani RDS, Yunita (PT Kimshafi Alung Cipta, 2025)
This study explores the relationship between transformational leadership style and employee performance, incorporating the mediating variable of work engagement. The intense competition in the industry requires companies to have solid business strategies and quality human resources (HR) to enhance employee performance. HR, being the core of company operations, requires continuous development through training to achieve the desired performance. Previous research indicates that employee performance can be influenced by various factors, including leadership style, compensation, motivation, and job satisfaction. Specifically, the transformational leadership style is considered to enhance performance by inspiring employees through a clear vision and proactive support. However, previous research has shown mixed results, with some studies finding significant positive effects, while others find no significant impact. Additionally, this study integrates work engagement as a mediating variable, which is a positive state of employees who are fully engaged and enthusiastic about their work. Past research shows that work engagement has a significant influence on performance improvement. In an effort to fill the gaps from previous research, this study aims to delve deeper into how transformational leadership style affects employee performance, considering the role of work engagement. It is crucial to verify whether integrating these factors can effectively enhance performance in a competitive context, as well as provide insights for future HR development strategy improvements.